The Influence of Live Streaming, Price Discount, and Online Customer Review on Purchase Intention of Somethinc Products (A Study on Students of UPN “Veteran” East Java as Consumers of Somethinc Products Shopping on Shopee) - Wirda Fitria Sahila; Siti Ning Farida (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to determine the significant influence of Live Streaming, Price Discount, and Online Customer Review both simultaneously and partially on consumer Purchase Intention for Somethinc products on the Shopee platform. This research is associative in nature with a quantitative approach. Variable measurement was conducted using a Likert scale with criteria ranging from strongly disagree to strongly agree. The sampling technique employed was probability sampling with a simple random sampling approach. The population in this study consists of active students at UPN